The Experience of Surgical Treatment of Shone’s Anomaly - E. Dovgaliuk; N. Rudenko; V. Hanenova; A. Dovgaliuk; I. Yemets (Ukrainian Journal of Cardiovascular Surgery, 2016)
We present the over experience of surgical treatment of 29 patients with Shone anomaly from 2004 to 2015 years. It is shown that in spite of the need for re-surgery, the prognosis for these patients is favorable.